2000
DOI: 10.1021/jp001614t
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Properties of the Mixed J-Aggregate of Two Kinds of Cyanine Dyes in Layer-by-Layer Alternate Assemblies

Abstract: The layer-by-layer alternate assemblies incorporating two kinds of cyanine dyes have been fabricated by alternately adsorbing a cationic polyelectrolyte and anionic cyanine dyes on the quartz plate. A thiacyanine dye (dye I) was employed as the donor and two kinds of thiacarbocyanine dye having a meso-alkyl groups m-ethyl (dye II), m-methyl (dye III)sas the acceptor. The mole fraction of the acceptor in the mixed J-aggregate, χ, was varied from 0 to 1. It is confirmed that these dye combinations form the mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 36 publications
3
76
0
1
Order By: Relevance
“…Absorption and fluorescence spectra of LB films on the quartz plate were measured by a V-530 spectrophotometer (JASCO) and a FP-750 fluorimeter (JASCO), respectively. Picosecond fluorescence lifetime measurements were carried out by the method of time-correlated single-photon counting as before [12]. Fluorescence decay curve was fitted to the multiple exponential function convoluted with the instrumental response function.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Absorption and fluorescence spectra of LB films on the quartz plate were measured by a V-530 spectrophotometer (JASCO) and a FP-750 fluorimeter (JASCO), respectively. Picosecond fluorescence lifetime measurements were carried out by the method of time-correlated single-photon counting as before [12]. Fluorescence decay curve was fitted to the multiple exponential function convoluted with the instrumental response function.…”
Section: Methodsmentioning
confidence: 99%
“…2 Therefore, we can state that energy transfer and trapping of molecular excitons obey the Stern -Volmer kinetics when small amount of S11 are doped into the S9(J). The rate constant of energy transfer k ET = 1.5 × 10 13 nm 2 molecules -1 s -1 is fairly large [12]. In view of the Stern -Volmer constant K SV = 1200 nm , it is suggested that the molecular exciton of S9(J) (N cohe = 22) can move over about 2000 donor molecules (incoherent size N inco = 2000) within the lifetime governed by quenching with S11.…”
Section: Original Papermentioning
confidence: 99%
See 1 more Smart Citation
“…A computational study of energy transfer and trapping in two-dimensional J-aggregates was performed in order to simulate the luminescent properties of such aggregates [7]. Recently, the luminescence properties, at room temperature, of mixed J-aggregates of two kinds of cyanine dyes were examined [8][9][10]. In general, these aggregates of finite size are characterized by relatively short stacking distances between the chromophores, leading to strong intermolecular interactions because of the long range dipole-dipole couplings.…”
mentioning
confidence: 99%
“…1, a) and its J-aggregates. This dye is well-known to form different kinds of J-aggregates in solution [10] [11] as well as in LB [12] and selfassembled [13] [14] films. The choice of THIATS allowed us to prepare a stable solution of J-aggregates and pre-PPV in H 2 O, while it was not possible for the dye 5,5',6,6'-tetrachloro-1,1'-diethyl-3,3'-bis(4-sulfobutyl)benzimidazolocarbocyanine (TDBC) [15] [16] due to incompatibility of the pH of the mixed compounds.…”
mentioning
confidence: 99%